2020
DOI: 10.1093/cid/ciaa737
|View full text |Cite
|
Sign up to set email alerts
|

Oral Capsulized Fecal Microbiota Transplantation for Eradication of Carbapenemase-producing Enterobacteriaceae Colonization With a Metagenomic Perspective

Abstract: Background Carbapenemase-producing Enterobacteriaceae (CPE) infections lead to considerable morbidity and mortality. We assessed the potential of fecal microbiota transplantation (FMT) to eradicate CPE carriage and aimed to explain failure or success through microbiome analyses. Methods In this prospective cohort study, all consenting eligible CPE carriers were treated with oral capsulized FMT for 2 days. The primary outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 21 publications
2
54
0
1
Order By: Relevance
“…This observation was in contrast to that in case-series studies, where PPIs (omeprazole and pentaprazole) were used in all studies as a pre-treatment in different time points, except in Leo et al. [ 49 ] Bowel cleansing was not conducted in any of the case studies/reports, but it has been applied in many case series studies [ 55–57 ]. Except in one case study [ 64 ], the FMTs in all included studies were procured from unrelated healthy donors.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…This observation was in contrast to that in case-series studies, where PPIs (omeprazole and pentaprazole) were used in all studies as a pre-treatment in different time points, except in Leo et al. [ 49 ] Bowel cleansing was not conducted in any of the case studies/reports, but it has been applied in many case series studies [ 55–57 ]. Except in one case study [ 64 ], the FMTs in all included studies were procured from unrelated healthy donors.…”
Section: Resultsmentioning
confidence: 91%
“…Out of fourteen studies, the majority are case reports or case studies ( n = 7) followed by different types of case series ( n = 5) and two ( n = 2) in vivo studies involving mice models. Out of the five case series studies, two ( n = 2) were carried out in multiple centres (Switzerland, Netherland, France, and Israel) [ 49 , 50 ], while the remaining ( n = 3) are single-center studies [ 55–57 ]. Most of the case reports/studies ( n = 5/7) were carried out in Europe; namely, Denmark ( n = 2) [ 58 , 59 ], Poland ( n = 2) [ 60 , 61 ], Netherland ( n = 1) [ 62 ], and one study each in USA [ 63 ] and South Africa [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An RCT reported that FMT using the capsules was not inferior to that using colonoscopic infusion in patients with recurrent CDI (capsule, 96.2% [51/53] vs colonoscopic infusion, 96.2% [50/52]; risk difference, 0%) [ 12 ]. Further, the capsule- mediated FMT was used for eradication of Carbapenemase-producing Enterobacteriaceae (CPE) colonization [ 13 ]. A total of 30 oral capsules, containing 25 to 30 g stool in total, were ingested during two consecutive days.…”
Section: Fmt With Next Generation Stool Formulationsmentioning
confidence: 99%
“…Changes in specific microbial taxa have been suggested as important factors for the efficacy of FMT, especially for non-CDI diseases. For instance, Bifidobacterium bifidum abundance has been reported to increase after FMT for CPE [ 13 ]. However, the bacterial composition after FMT differed between those who showed remission (FMT responders) and lack of remission (non-responders) in UC patients [ 29 ].…”
Section: Precision Medicinementioning
confidence: 99%